Comparison of Solubility of Corn Proteins in Propanol, Ethanol, and tert‐Butyl Alcohol Solutions on the Tortilla Process Samples. Issue 6 (5th September 2017) - Chaidez‐Laguna, Leslie D.; Torres‐Chávez, Patricia I.; Ramirez‐Wong, Benjamin; Medina‐Rodríguez, Concepción L.; Carvajal‐Millán, Elizabeth
Abstract : To find the best solvent of those reported and to study changes in protein aggregation during corn processing to obtain tortillas, extractability of corn proteins with three alcoholic solutions (70% ethanol, 50% propanol, and 60% tert ‐butyl alcohol) was compared in corn, nixtamal, masa, and tortillas. Relative solubility was assessed through size‐exclusion chromatography, SDS‐PAGE, and insoluble polymeric protein determination using the Dumas procedure. Differences in the behavior of solvents in the samples indicate that different protein interactions are promoted during each of the processing steps. All the three alcoholic solutions can be used to study changes in corn proteins, but the best solvent was 50% propanol. Ethanol (70%) extracted the lowest amounts of corn proteins in tortilla process samples.